SPAWNING AND RECRUITMENT AREAS OF MIGRATORY FISH IN THE URUGUAY RIVER: APPLYING FOR RIVERS CONNECTIVITY CONSERVATION IN SOUTH AMERICA - Carlos Eduardo Mounic-SILVA; Carolina Antonieta LOPES; Leonardo Bracony Porto-FERREIRA; Mayara Esmeraldino NUNES; David Augusto Reynalte-TATAJE; Evoy Zaniboni-FILHO (Boletim do Instituto de Pesca)
Identifying spawning and recruitment areas of Neotropical migratory fish is an important conservation issue, because it allows to define connectivity between habitats used during the initial life cycle of these species. In this sense, the objective of this study was to delimit spawning and recruitment areas of three migratory fish (Megaleporinus obtusidens, Salminus brasiliensis and Prochilodus lineatus) along of an altitude gradient of the Uruguay River. Samplings of ichthyoplankton and juveniles were applied with five different fishing devices in four river stretches, one in reservoir and three in a free section, for two consecutive years (2015-2016 and 2016-2017), during the reproductive period of the species. Larvae and juveniles were not collected in the reservoir and, in the free section, larvae in the early stages of development were found only at an intermediate stretch, and the most larvae at more advanced stages (~80%) and juveniles (~95%) were recorded in the lower sampling stretch. Based on the larval stage and abundance of juveniles, spawning-recruitment connectivity sections were presumed for these migratory species. After, these sections were associated to the location of future hydroelectric dams in the study area, with possible negative implications for the conservation of these populations in the Uruguay River.